Profile of Extracurricular Physical Condition of Kickboxing and Muaythai Students of SMA Negeri 1 Ngawi - Fantas Setyadi (Universitas Muhammadiyah Enrekang, 2023)
Physical condition is very necessary for professional and amateur class athletes, this is because physical condition will affect the performance of athletes. This study aims to determine the profile of the physical condition of students participating in extracurricular kickboxing and Muaythai at SMAN 1 Ngawi. The type of research used in this study is quantitative descriptive. This study used a data collection survey using measurement tests. The population of the study was 20 students from 10 extracurricular kickboxing participants and 10 Muaythai extracurricular participants, and total sampling was used in this study. Research using the instruments used, namely abdominal muscle strength using (Sit Up), leg muscle strength using (Standing Board Jump), arm muscle strength using (Push Up), speed using (Sprint 30m), flex using (Sit and Reach), power using (Vertical Jump), agility using (Illinois Run Test), and endurance using (MFT). The data analysis uses descriptive percentages. The results showed the profile of the physical condition of students participating in the extracurricular kickboxing SMAN 1 Ngawi in the